Correction: Nationwide survey for current clinical status of amniocentesis and maternal serum marker test in Japan. Issue 11 (November 2018) - Miyake, Hidehiko; Yamada, Shigehito; Fujii, Yosuke; Sawai, Hideaki; Arimori, Naoko; Yamanouchi, Yasuko; Ozasa, Yuka; Kanai, Makoto; Sago, Haruhiko; Sekizawa, Akihiko; Takada, Fumio; Masuzaki, Hideaki; et al.
Since the publication of this paper, the authors noticed that Yosuke Fujii was assigned to the incorrect affiliation. The affiliation information is provided correctly, above.